Fatal Fulminant Hepatic Failure in a Diabetic with Primary Dengue - Stalin Viswanathan; Nayyar Iqbal; P. Philip Anemon; G. Shyam Kumar (Journal of Tropical Medicine)
We report a 49-year-old diabetic with dengue hemorrhagic fever who developed fulminant hepatitis, severe coagulopathy, shock, and refractory metabolic acidosis and died on the eighth day of illness. This is the only second report of an adult with fatal fulminant hepatic failure due to dengue, and the first case arising from a primary dengue infection.